Analisis Tingkat Kecelakaan Lalu Lintas di Ruas Jalan Sukowati Kabupaten Sragen - Pamuji, Febriyanto Setio; , Drs. Gotot Slamet Mulyono, MT (2018)
Sragen Regency constitute province center java the have number of people 978.590 people (BPS, 2016). The increasing of number of people in Sragen Regency make the need of transportation in also increased so is it unavoidably the number of accident occurred ever year. It is condition needs an effort to identify the rank traffic accidents, black site and measure toreduce traffic accidentns. The research used secondary data accident data from local police department from the year 2012 until 2015. The analyses conducted include the number of accident to find out the black site with EAN (Equivalent Accident Number) method and EPDO (Equivalent Property Demage Only) method. Crash rank accidents analysis using the method of number ekuivalen accident (AEK). The number accident on Sukowati (Km.Ska 30+260 - Km.Ska 33+860) are 183 incident, where on number peope death 57 people, serious injury 74 people, and minor in importance injury 109 people. Based on secondary data know black site it was obtained section in Sukowati as black site location on Sukowati (Km. 31+260 - Km. 31+760) obtain EAN of 225 and Sukowati (Km. 31+260 - Km. 31+760) obtain EPDO of 328. Based on the rangking of crash sites obtained the highest rangking that is on Sukowati road (Km. 31+260 - Km. 31+760) obtain of 283. Measure to reduce accident on black spot 3E approach is engineering include installed zebra cross, road stud, rumble strip, delineator, light signing, etc. Education included road safety campaign and traffic safety education since the dominant accidents caused by human factor, namely the driver. The last one is enforcement included law enforcement. Keyword : Black site, accident flow, traffic